Challenges of integrated modelling in mining regions to address social, environmental and economic impacts. (July 2017) - Lechner, Alex M.; McIntyre, Neil; Witt, Katherine; Raymond, Christopher M.; Arnold, Sven; Scott, Margaretha; Rifkin, Will
Abstract: Planning in mining regions needs to accommodate the extraction of minerals/energy resources in co-existence with established land uses, such as agriculture and ecological conservation. Here, we first identify six critical aspects of planning in mining regions: i) the temporal nature of mining operations; ii) spatial dimensions of mining operations; iii) irreversible changes that create post-mining landscapes; iv) social dimensions of mining impacts and corporate responsibility; v) cumulative dimensions of impacts; and vi) a need to integrate methods from a range of disciplines. We then illustrate the potential to address these challenges using integrative modelling nested within a participatory approach to allow for clear, transparent, and stakeholder-inclusive decision-making. We describe a 5-step framework that supports a broadening of strategic assessments and offers mining companies forewarning about potential environmental and social conflicts. Case studies are needed to assess and refine the proposed framework and develop guidance for its use. Graphical abstract: Highlights: Planning for mining regions needs to accommodate multiple established land uses. Five aspects of mining affect the application of integrated regional modelling. We describe an integrated, multi-disciplinary modelling approach for mining regions. Such modelling and decision making need to be participatory in order to reduce conflict. This framework supports a broadening of strategic assessments for mining.